SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU SMA NEGERI 1 NGEMPLAK KABUPATEN BOYOLALI - Iwan Ady Prabowo (Jurnal Ilmiah SINUS, 2015)
Senior High School (SMA) Negeri 1 Ngemplak one of the many schools in Boyolali, the announcement about the acceptance of new students (PPDB) still uses a circular brochure. To be able to provide information services to prospective new students as consumers in Ngemplak and the general public in order to promote SMA Negeri 1 Ngemplak needed an information system as a means of delivering information to the public in the form of information systems Acceptance New Students (PPDB).The purpose of this research is to make the information system admission of new students (PPDB) into a web-based computer applications, because ofthat the existing system more effective and efficient future can facilitate the operational service of reception of new students at SMA Negeri 1 Ngemplak Keyword: admission of new students, school information system